Parental Perceptions and Attitudes Toward Overweight and Obesity Among Their Preschool Children In Holy Kerbela City - alsaadi, ahmed mahdi (Karbala Journal of Medicine, 2020)
The World health organization has stated that obesity is a public health problem, and because obesity has its onset very early in life; therefore, children constitute a major group of this disease. The preschool years are critically important for child health, developmental, learning and social outcomes. WHO view the prevention of childhood obesity as a ‘high priority’ with parents being seen as influential in child weight-related behaviors, the first step in treating obesity is to identify overweight, how parents perceived their overweight and obese children, and their attitudes regarding obesity among their children. Objectives: - To estimate the prevalence of overweight and obesity among preschool children in Karbala city. understanding how a parent perceive their children’s weight status, whether or not the parents perceived the Causes and consequences of overweight and obesity and to assess parental attitudes toward overweight and obesity. Methods: - A cross- sectional study was carried out in a five governmental and five private kindergartens in holy Kerbela city between the 1st of February to the 30th of June 2017, with a total number of 200 children aged 45 to 60 months were included. the weight and height was estimated for each child and a questionnaire paper were filled by the parents in order to identify their perception and attitudes towards overweight and obesity in their children. Results: - The prevalence of overweight was 20 % and of obesity was 18.5%, there was a highly significant relationship between weight status of the children and their parents, as about 85 % of overweight and obese children, had obese and overweight fathers and mothers. 60 % of all parent prefer that their child being overweight or obese rather than being low or underweight also more than half of the parents found to had negative attitudes towards their child body image. there was a highly significant relationship between parental perception and their concern for their children to became overweight in the future. Conclusions: - We can conclude that the prevalence of overweight and obesity was relatively high among preschool children in Holy Kerbela city. parental misperception of their children's weight status was highest among parents of overweight and obese children, and accurate perception is necessary as a first step for establishing behavioral modification goals for diet and physical activity for children’s health, also the study revealed that parental perception will affect parental concern and lead to life style modifications. Key words: childhood overweight and obesity, Parental Perceptions and Attitudes